An artificial nesting substrate for Osmia species that nest under stones, with focus on Osmia inermis (Hymenoptera: Megachilidae). Issue 2 (17th October 2014) - Sheffield, Cory S.; Wilkes, Margie A.; Christopher Cutler, G.; Hermanutz, Luise; Schonrogge, Karsten; Packer, Laurence
Abstract Several megachilid bees are excellent crop pollinators, and many species show potential for management as they nest in pre‐existing cavities in artificial substrates. Some species, particularly in the Osmiini, however, have nesting habits not conducive to conventional trap‐nesting. Here we report on an artificial nest for species of Osmia bees which normally build nests on the underside of stones. The Holarctic species Osmia inermis accepted overturned terracotta saucers as nesting sites, with 10% of the saucers occupied in the fall of 2011. These saucers are inexpensive and available in many sizes, facilitating further scientific study of this, and other species. Implications of using artificial nests for managing this bee for crop pollination, and for its conservation, are discussed.